Primary health care seeking behaviour of people with physical disabilities in Bangladesh: A cross-sectional study - Talukdar, Jhalok Ronjan; Mahmud, Ilias; Rashid, Sabina Faiz (BMC, 2022)
This article was published in the BMC © The Author(s). 2018 Open Access This article is distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/) ] and the definite version is available at: https://doi.org/10.1186/s13690-018-0293-1 The Journal's website is at: https://archpublichealth.biomedcentral.com/articles/10.1186/s13690-018-0293-1#citeas